PENGARUH TELEWORKING, WORK LIFE BALANCE, DAN STRES KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA PT SRIWIJAYA AIR TANGERANG) - Nadhira Ramadhya Salma (2022)
This research is quantitative research that aims to determine the effect of teleworking, work life balance, and work stress on employee performance. This study used 93 employees of PT Sriwijaya Air Tangerang, using a simple random sampling technique. The analysis technique used is path analysis and the data is processed using SmartPLS 3.0. The results of the test obtained: (1) teleworking has a positive and significant effect on the performance of employees of PT Sriwijaya Air Tangerang, (2) work life balance has a positive and significant effect on the performance of employees of PT Sriwijaya Air Tangerang, and (3) work stress has a significant effect on performance employees of PT Sriwijaya Air Tangerang, (2) work life balance has a negative and significant effect on the performance of employees of PT Sriwijaya Air Tangerang.